A single-centre experience of implementing a rapid CXR reporting and CT access pathway for suspected lung cancer: Initial outcomes. Issue 2 (May 2022) - Hunter, R.; Wilkinson, E.; Snaith, B.
Abstract: Introduction: Lung cancer remains a major cause of preventable death and early diagnosis is critical to improving survival chances. The chest X-ray (CXR) remains the most common initial investigation, but clinical pathways need to support timely diagnosis through, where necessary, escalation of abnormal findings to ensure priority reporting and early CT scan. Methods: This single-centre study included a retrospective evaluation of a rapid lung cancer CXR pathway in its first year of operation (May 2018–April 2019). The pathway was initially designed for primary care referrals but could also be used for any CXR demonstrating abnormal findings. A parallel cross-sectional survey of radiographers explored their understanding, adherence and concerns regarding their role in the pathway operation. Results: Primary care referrals on the rapid diagnostic pathway were low (n = 51/21, 980; 0.2%), with 11 (21.6%) requiring a CT scan. A further 333 primary care CXR were escalated by the examining radiographer, with 100 (30.0%) undergoing a CT scan. Overall, 64 of the CT scans (57.7%) were abnormal or demonstrated suspicious findings warranting further investigation. There were 39 confirmed primary lung carcinomas, most with advanced disease. Survey responses showed that most radiographers were familiar with the pathway but some expressed concerns regarding their responsibilities and limited knowledge of CXR pathologies. Conclusion: This baseline evaluation of the rapid lung cancer pathway demonstrated poor referral rates from primary care and identified the need for improved engagement. Radiographer escalation of abnormal findings is an effective adjunct but underlines the need for appropriate awareness, training, and ongoing support. Implications for practice: Engagement of the multiprofessional team is critical in new pathway implementation. Rapid diagnostic pathways can enable early diagnosis and the radiographer has a key role to play in their success.